Minimal Influence of Hypobaria on Heart Rate Variability in Hypoxia and Normoxia - Aebi, Mathias Roland; Bourdillon, Nicolas; Bron, Denis; Millet, Grégoire P. (Frontiers in Physiology, 2020)
Introduction: The present study evaluated the putative effect of hypobaria on resting HRV in normoxia and hypoxia. Methods: Fifteen young pilot trainees were exposed to five different conditions in a randomized order: normobaric normoxia (NN, PB=726±5 mmHg, FIO2=20.9%), hypobaric normoxia (HN, PB=380±6 mmHg, FIO2≅40%), normobaric hypoxia (NH, PB=725±4 mmHg, FIO2≅11%); and hypobaric hypoxia (HH at 3000 m and 5500 m, HH3000 and HH5500, PB=525±6 and 380±8 mmHg, respectively, FIO2=20.9%). HRV and pulse arterial oxygen saturation (SpO2) were measured at rest seated during a 6-min period in each condition. HRV parameters were analysed (Kubios HVR Standard, V 3.0) for time (RMSSD) and frequency (LF, HF, LF/HF ratio, and total power). Gas exchanges were collected at rest for 10 minutes following HRV recording. Results: SpO2 decreased in HH3000 (95±3) and HH5500 (81±5), when compared to NN (99±0). SpO2 was higher in NH (86±4) than HH5500 but similar between HN (98±2) and NN. Participants showed lower RMSSD and total power values in NH and HH5500 when compared to NN. In hypoxia, LF/HF ratio was greater in HH5500 than NH, whereas in normoxia, LF/HF ratio was lower in HN than NN. Minute ventilation was higher in HH5500 than in all other conditions. Discussion: The present study reports a slight hypobaric effect either in normoxia or in hypoxia on some HRV parameters. In hypoxia, with a more prominent sympathetic activation, the hypobaric effect is likely due to the greater ventilation stimulus and larger desaturation. In normoxia, the HRV differences may come from the hyperoxic breathing and slight breathing pattern change due to hypobaria in HN.